An investigation into the nature and prevalence of musculoskeletal conditions among women attending a community clinic, and the effectiveness of an intervention programme for these patients - Barnes, Roline Yvette (Department of Health and Rehabilitation Sciences, 2017)
The thesis set out to document the process of developing and testing a non-pharmacological biopsychosocial intervention programme which included exercise and health education for women with musculoskeletal conditions attending a clinic in a poorly resourced area of the Free State Province in South Africa. To inform the development of an appropriate intervention, several sub-studies were undertaken. Systematic reviews on the use of exercise and health education in adults were undertaken, one on the impact of these interventions on adults with chronic diseases of lifestyle (diabetes mellitus type II, hypertension) and the risk factor obesity, and the other on the impact on adults with musculoskeletal conditions. The selected research tools, which were chosen based on the framework of the International Classification of Functioning, Disability and Health (ICF) were subjected to a rigorous translation process. A facility-based descriptive observational cross-sectional study was undertaken to determine the prevalence and nature of musculoskeletal conditions amongst women between the ages of 40 and 64 years attending a community clinic. The gathered information was then used to modify and adapt existing non-pharmacological programmes and develop an intervention programme tailor made for these patients. Finally, an experimental randomised controlled trial was undertaken to determine the effectiveness of usual care against a non-pharmacological intervention utilising a workbook for the women identified in the survey.